‘When Teachers Become Students’: Enhancing the Engagement of Public Senior High School XY Kediri Teachers During Online Learning - Yogie Andreas; Putri Ayu Wiwik Wulandari; Lena Nessyana Pandjaitan (Psikostudia : Jurnal Psikologi, 2021)
Online learning during the pandemic has reduced teacher engagement at SMAN XY Kediri. The 'When Teachers Become Students' training was to foster teacher engagement. This training used a Sense of Self-efficacy approach (instructional strategies, classroom management, & student engagement). This study used a quantitative approach with the experimental method of pretest-posttest design. The sampling technique used is purposive sampling with a total of 16 participants. Measurements were given before and after the training consisting of the engaged teacher scale by Klassen, Yerdelen, and Durksen (2013). Data were analyzed using paired sample t-test. There was an increase in the score of sense of self-efficacy (sig 0.00 (p<0.05)). It indicates that this training is quite effective in increasing teacher engagement at SMA XY Kediri.